Word of Mouth, Price, and Image: Factors Shaping Makeup Service Decisions.: Pengaruh Mulut ke Mulut, Harga, dan Citra Perusahaan terhadap Keputusan Memilih Layanan Makeup - Amelia Rifaatur Rizky; Mudji Astuti (Academia Open, 2022)
This quantitative study investigates the factors influencing consumer decision making in the context of declining consumer usage of Tiara Sanggar Rias services. The research aims to determine, explain, and analyze the effects of Word of Mouth, Price, and Company Image on the decision to choose these services. A questionnaire-based survey was conducted with 100 respondents who have utilized Tiara Sanggar Rias services. The collected data were analyzed using multiple linear regression in SPSS version 18. The findings reveal that Word of Mouth, Price, and Company Image individually influence consumer decisions, while collectively, these variables significantly impact purchasing choices. The implications of this research emphasize the importance of managing customer perceptions, enhancing positive word of mouth, pricing strategies, and improving company image to attract and retain consumers. This study contributes to the understanding of consumer behavior and provides valuable insights for service providers aiming to optimize their marketing strategies. Highlights: Word of Mouth: Influential factor in choosing makeup services due to recommendations. Price: Consideration of cost affordability in the decision-making process. Company Image: Reputation and perception of the makeup service provider impacting the choice. Keywords: Word of Mouth, Price, Company Image, Makeup Services, Decision.